Upaya Upaya Meningkatkan Kemampuan Senam Lantai Guling Depan Dengan Menggunakan Metode Pendekatan Jigsaw Pada Siswa Kelas IX C SMP Negeri 22 Semarang Tahun Pelajaran 2023/2024 - Hardiansyah, Fernanda (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research was conducted to overcome the unmet criteria for completeness in learning front-rolling gymnastics in class IX C SMP N 22 Semarang. This research aimed to improve the learning of front rolling through the Jigsaw approach in class IX C SMP N 22 Semarang. This research is a classroom action research consisting of two cycles, each consisting of two meetings. The research subjects were 33 students of class IX C SMP N 22 Semarang (14 boys and 19 girls). The data collection instruments used include observation, questionnaire, and front roll learning outcomes test. Data analysis techniques were carried out qualitatively and quantitatively. The results showed that the Jigsaw approach can improve front-roll learning in class IX C SMP N 22 Semarang students. Based on the analysis conducted by collaborators and researchers, the value in Cycle I was 54% and in Cycle II reached 100%, so it can be concluded that learning floor exercises through the Jigsaw approach has increased in class IX C SMP N 22 Semarang.